2020
DOI: 10.1007/s00402-020-03420-8
|View full text |Cite|
|
Sign up to set email alerts
|

Patellar fixation graft via suture anchors versus tunnel techniques during isolated MPFL reconstruction for recurrent patellofemoral instability: a systematic review of the literature

Abstract: Introduction There is still a lack of evidence concerning the patellar fixation of the medial patellofemoral ligament (MPFL) graft in selected patient with recurrent instability. The purpose of the present study was to investigate and compare clinical outcomes and further complications of isolated MPFL reconstruction via suture anchors versus tunnel techniques for recurrent patellofemoral instability. Materials and methods This systematic review of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…The number of bundles, type of fixation, and graft tensioning for MPFL reconstruction in patients with patellofemoral instability is still debated [2,8,10,37,[52][53][54][55][56][57][58]. Thus, several variations and combinations of procedures have been described.…”
Section: Discussionmentioning
confidence: 99%
“…The number of bundles, type of fixation, and graft tensioning for MPFL reconstruction in patients with patellofemoral instability is still debated [2,8,10,37,[52][53][54][55][56][57][58]. Thus, several variations and combinations of procedures have been described.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with patellar chondral defects, pathoanatomical tissue morphology predisposing to patellofemoral instability (PFI) must be investigated [55,56]. Chondral defects are common in patients who experienced a patellar dislocation, [57][58][59][60][61][62]. Up to 96% of patients after patellar dislocation experience chondral damages [63][64][65][66].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, many authors have found more complications related to the use of patellar bone tunnels, especially patellar fractures, and persistent pain. 17,[20][21][22][23][24][25]38,39 Desai et al, 1 in their systematic review, showed rates of patellar fractures between 0% and 17%, significantly higher in bone tunnel techniques, despite the fact that the clinical outcomes are similar to those of cortical fixation techniques. The risk of fracture increases as the tunnel size increases, especially for those > 4.5 mm, as seen with EndoButton techniques.…”
Section: Discussionmentioning
confidence: 99%
“…12 Common patellar fixation techniques for MPFLR include anchors, bone tunnels, and interference screws. [16][17][18][19] Studies comparing fixation methods show a higher risk of patellar fracture in bone tunnel techniques. 17,[20][21][22][23][24][25] Transosseous sutures have been described also for MPFLR with single-bundle reconstruction, 26 but no clinical studies were found for double-bundle reconstruction.…”
Section: Palabras Clavementioning
confidence: 99%